Preparation the porous hollow fibers based on parameter optimization of coaxial electrospinning techniques for cell growth inside - Liu, Zhen (2018)
Electrospinning is widely used because it can produce the three-dimensional (3D) structures that mimic the extracellular matrix. One of the problems limiting the use of electrospun fibrous scaffolds is that the small pores prevent the infiltration of cells and the fusion between scaffolds and the host cells. In order to improve this phenomenon, using a new coaxial electrospinning method, this dissertation first explores the influence of humidity on pore size for uniaxial fiber and then explodes the process parameter (voltage and PCL concentration) on the coaxial nanofibers with PCL as shell and PVA as core during the process. By optimizing the conditions, uniform microfibers with an average diameter of 86.650 μm were obtained using a flow rate of 30 ml/h for PCL and 10ml/h for PVA with a voltage of 9 kV. Then, the effect of ambient humidity on the voids of the coaxial PCL fibers was explored emphatically. The results showed that the morphology and porosity of fibers depend on the polymer PCL concentration and relative humidity. The highest porosity and good pore size were obtained at the relative humidity of 90% and PCL concentration of 20 %. Finally, the coaxial microfibers with PCL as sheath and PVA with PC12 cells as core were prepared. After dissolving the PVA, PC12 cells were successfully cultured inside the hollow PCL fiber scaffolds with high porosity. We experimentally confirmed that the cells in the 3D hollow scaffolds can grow, proliferate well.